2011
DOI: 10.1021/ic200653d
|View full text |Cite
|
Sign up to set email alerts
|

Smart Heterostructures for Tailoring the Optical Properties of Photochromic Hybrid Organic–Inorganic Polyoxometalates

Abstract: A new concept of photoresponsive composites has been elaborated by intimately connecting a Photochromic Phase (PP), (H(2)DABCO)(2)(HDMA)(0.5)Na(0.75)(H(3)O)(0.75)[Mo(8)O(27)]·3H(2)O (1), with a second hybrid organic-inorganic molybdate material, (H(2)DABCO)(HDABCO)[Fe(OH)(6)Mo(6)O(18)]·4H(2)O (2) acting as an Oxidation Catalytic Phase (OCP) toward the former once photoexcited. The association of both the PP and the OCP in the composite drastically improves the bleaching process of the PP alone because of effic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
38
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(38 citation statements)
references
References 33 publications
0
38
0
Order By: Relevance
“…Control experiments revealed that presence of Co is essential for catalytic activity but also that Co metal centers with higher nuclearity in other POM archetypes are not necessary to attain high catalytic activity as the mononuclear Co center in the Anderson-Evans POM can also serve as O 2 -evolving catalyst. The (H 2 DABCO)(HDABCO)[Fe(OH) 6 [Mo 8 O 27 ] one of the most efficient photochromic Mo-POM materials in regard to coloration contrast and coloration speed [224].…”
Section: Photocatalytic Propertiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Control experiments revealed that presence of Co is essential for catalytic activity but also that Co metal centers with higher nuclearity in other POM archetypes are not necessary to attain high catalytic activity as the mononuclear Co center in the Anderson-Evans POM can also serve as O 2 -evolving catalyst. The (H 2 DABCO)(HDABCO)[Fe(OH) 6 [Mo 8 O 27 ] one of the most efficient photochromic Mo-POM materials in regard to coloration contrast and coloration speed [224].…”
Section: Photocatalytic Propertiesmentioning
confidence: 99%
“…Mo 6 [93,175,[218][219][220], Co II/III Mo6 [221][222][223] FeIII Mo 6 [224], Cu II Mo6 [174,[225][226][227][228][229], Zn II Mo6 [230], AsIII Mo 6 [229][230][231][232],Mo 7 [112,176,193,[233][234][235][236][237][238][239][240][241][242][243][244][245], Te VI Mo6 [70,[246][247][248][249][250], Te VI W 6[70,75,[251][252]…”
mentioning
confidence: 99%
“…Also cucurbituril-POMs dyads [246] exhibit reversible photochromic properties as well as excellent photocatalytic activities toward the degradation of methyl orange (MO) and rhodamine-B (RB) under visible light irradiation. Interconversion pathways and chemical factors affecting the stabilization of the different species are highlighted and discussed in hybrids based on DABCO, [247] piperazine and molybdate. [248] Some exotic systems such as 3D iodoplumbate open-framework material exhibited interesting wavelengthdependent photochromic properties.…”
Section: Q9mentioning
confidence: 99%
“…Understanding and applying the underlying principles for the design of biomimetic and engineered materials may guide materials science towards sustainable, renewable, and smart materials. Photochromic materials, which change their colors reversibly in response to light, can be used for many applications, such as smart windows, displays, and memories [9,10]. So far, a photochromic coating has been developed by some inorganic oxides coating on some substrates [11][12][13][14].…”
Section: Introductionmentioning
confidence: 99%